Docosahexaenoic and Eicosapentaenoic Intervention Modifies Plasma and Erythrocyte Omega-3 Fatty Acid Profiles But Not the Clinical Course of Children With Autism Spectrum Disorder: A Randomized Control Trial - de la Torre-Aguilar, Maria Jose; Gomez-Fernandez, Antonio; Flores-Rojas, Katherine; Martin-Borreguero, Pilar; Mesa, María Dolores; Perez-Navero, Juan Luis; Olivares, Mónica; Gil, Angel; Gil-Campos, Mercedes (Frontiers in Nutrition, 2022)
Background: The pathogenesis of autism spectrum disorder (ASD) is under investigation and one of the main alterations relates to metabolic and inflammatory dysfunctions. Indeed, based on a deficit of omega-3 fatty acids (FA) of ASD patients and looking for an anti-inflammatory effect, dietary supplements with omega-3 fatty acids have been proposed. We aimed to evaluate differences in plasma and erythrocyte FA profiles and plasma cytokines in ASD children after supplementation with docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids or placebo and both compared at baseline with a reference healthy group. Methods: A double-blind, randomized placebo-controlled intervention with DHA/EPA for six months was carried out in 54 ASD (2-6 years). They were random: 19 children received 800mg/day of DHA and 25mg/day of EPA, or placebo. Also, another 59 healthy children were included. Plasma lipids and cytokines, and FA profiles in plasma and erythrocytes were measured at baseline and after six months of treatment in ASD children, and at baseline in the reference group. Results: There were no differences in demographic, anthropometric characteristics and omega-3 intake between the healthy reference group and the ASD children at baseline. Children with ASD showed higher plasma percentages of palmitic acid and total saturated FA and lower total omega-6 polyunsaturated FA (PUFA) compared with healthy children. Increased level of DHA and reduced EPA level in erythrocytes was detected in the ASD group versus the reference group. After six months of treatment, the ASD group that received DHA enriched product significantly increased the plasma and erythrocyte percentages of DHA, but no differences were observed in the clinical test scores and other parameters as plasma cytokines between the two groups of ASD related to the intervention. Conclusion: Spanish children with ASD exhibit an appropriate omega-3 FA status in plasma and erythrocytes. Neither a clinical improvement of ASD children nor a better anti-inflammatory or fatty acid state has been found after an intervention with DHA/EPA for 6 months. So, the prescription of n-3 LC-PUFA and other dietary supplements in ASD should be only indicated after a confirmed alteration of FA metabolism or omega-3 LC-PUFA deficiency evaluated by specific erythrocyte FA’